Enhanced responsivity and detectivity of fast WSe2 phototransistor using electrostatically tunable in-plane lateral p-n homojunction - Sayantan Ghosh (Nature Portfolio, 2021)
In photodetectors based on 2D materials, a trade-off often exists between responsivity and speed. Here, the authors attenuate this issue via integration of a lateral, in-plane, electrostatically tunable p-n homojunction with a conventional WSe2 phototransistor.